Autophagy-independent function of Atg1 for apoptosis-induced compensatory proliferation. Issue 1 (December 2016) - Li, Mingli; Lindblad, Jillian; Perez, Ernesto; Bergmann, Andreas; Fan, Yun
Abstract Background ATG1 belongs to the Uncoordinated-51-like kinase protein family. Members of this family are best characterized for roles in macroautophagy and neuronal development. Apoptosis-induced proliferation (AiP) is a caspase-directed and JNK-dependent process which is involved in tissue repair and regeneration after massive stress-induced apoptotic cell loss. Under certain conditions, AiP can cause tissue overgrowth with implications for cancer. Results Here, we show thatAtg1 inDrosophila (dAtg1 ) has a previously unrecognized function for both regenerative and overgrowth-promoting AiP in eye and wing imaginal discs.dAtg1 acts genetically downstream of and is transcriptionally induced by JNK activity, and it is required for JNK-dependent production of mitogens such as Wingless for AiP. Interestingly, this function ofdAtg1 in AiP is independent of its roles in autophagy and in neuronal development. Conclusion In addition to a role ofdAtg1 in autophagy and neuronal development, we report a third function ofdAtg1 for AiP.